2022
DOI: 10.1080/00325481.2022.2033563
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic role of immunomodulators during the COVID-19 pandemic– a narrative review

Abstract: The emergency state caused by COVID-19 saw the use of immunomodulators despite the absence of robust research. To date, the results of relatively few randomized controlled trials have been published, and methodological approaches are riddled with bias and heterogeneity. Anti-SARS-CoV-2 antibodies, convalescent plasma and the JAK inhibitor baricitinib have gained Emergency Use Authorizations and tentative recommendations for their use in clinical practice alone or in combination with other therapies. Anti-SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 207 publications
(203 reference statements)
0
8
0
Order By: Relevance
“…Critical and severe COVID-19 forms, constituting 2–5% and 15% of cases, respectively, are assumed to occur from SARS-CoV-2-induced autoinflammatory syndrome, both at systemic and pulmonary levels, in which a dysregulated immune response, due to overflowing cytokine production and release, leads to widespread tissue and vascular damages [ 30 ]. Viral infections and autoimmune pathologies are known to be correlated to an abnormal immune response known as a “cytokine storm”, characterized by an excessive release of pro-inflammatory cytokines [ 31 , 32 ]. Host tissue toxicity, multiple-organ failure, and high fever are the most common effects of this syndrome, which could result in a fatal outcome.…”
Section: Cytokine Storm and Rationale For Il-6 Inhibitor Administrati...mentioning
confidence: 99%
“…Critical and severe COVID-19 forms, constituting 2–5% and 15% of cases, respectively, are assumed to occur from SARS-CoV-2-induced autoinflammatory syndrome, both at systemic and pulmonary levels, in which a dysregulated immune response, due to overflowing cytokine production and release, leads to widespread tissue and vascular damages [ 30 ]. Viral infections and autoimmune pathologies are known to be correlated to an abnormal immune response known as a “cytokine storm”, characterized by an excessive release of pro-inflammatory cytokines [ 31 , 32 ]. Host tissue toxicity, multiple-organ failure, and high fever are the most common effects of this syndrome, which could result in a fatal outcome.…”
Section: Cytokine Storm and Rationale For Il-6 Inhibitor Administrati...mentioning
confidence: 99%
“…The largest RCTs on the clinical efficacy of TCZ are the RECOVERY and REMAP-CAP trials, both of which demonstrated mortality benefits and a decrease in mechanical ventilation therapy. The RECOVERY trial clearly reported the efficacy of combined TCZ and DEX in comparison with DEX monotherapy, with mortality rates of 29% and 35%, respectively [ 84 ].…”
Section: Immune Modulator Therapiesmentioning
confidence: 99%
“…While those combination therapies with both or more biomacromolecules, like antibody, nanobody, convalescent plasma or some other therapeutic proteins like interferon, are not included. You may read another relative review for this kind of combination therapies [43]. We deem that this review would provide an option for the scientific and rational therapeutic alliance against COVID-19.…”
Section: Combination Therapy As a Treatment Strategy Blocking One Or ...mentioning
confidence: 99%